In Vitro and In Vivo Studies of Oritavancin and Fosfomycin Synergism against Vancomycin-Resistant Enterococcus faecium - Cristina Lagatolla; Jai W. Mehat; Roberto Marcello La Ragione; Roberto Luzzati; Stefano Di Bella (MDPI AG, 2022)
Therapeutic options for infections caused by vancomycin-resistant enterococci are currently suboptimal. Combination regimens where fosfomycin is used alongside existing treatments are emerging given the proven synergistic potential and PK/PD properties. In the studies presented here, we tested five vanA and five vanB clinical isolates of Enterococcus faecium using a combination of oritavancin + fosfomycin both in vitro (checkerboard, time killing) and in vivo (Galleria mellonella). The combination of oritavancin and fosfomycin increased drug susceptibility, showing a synergistic effect in 80% of isolates and an additive effect in the remaining isolates. The combination restored fosfomycin susceptibility in 85% of fosfomycin-resistant isolates. Time killing on four selected isolates demonstrated that the combination of oritavancin and fosfomycin provided a CFU/mL reduction > 2 log10 compared with the most effective drug alone and prevented the bacterial regrowth seen after 8-24 h at sub-inhibitory drug concentrations. In addition, the combination was also tested in a biofilm assay with two isolates, and a strong synergistic effect was observed in one isolate and an additive effect in the other. Finally, we demonstrated in vivo (Galleria mellonella) a higher survival rate of the larvae treated with the combination therapy compared to monotherapy (fosfomycin or oritavancin alone). Our study provides preclinical evidence to support trials combining oritavancin and fosfomycin for VRE BSI in humans, even when biofilm is involved.